2004
DOI: 10.1093/deafed/enh010
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Testing of Sign Language Interpreters

Abstract: Twenty-eight sign language interpreters participated in a battery of tests to determine if a profile of cognitive, motor, attention, and personality attributes might distinguish them as a group and at different credential levels. Eight interpreters held Level II and nine held Level III Virginia Quality Assurance Screenings (VQAS); the other 11 held Registry of Interpreters for the Deaf (RID) certification. Six formal tests, the Quick Neurological Screening Test-II, the Wonderlic Personnel Test, the Test of Vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
1
13
0
2
Order By: Relevance
“…The verbal Similarities task measures abstract verbal reasoning and analogical thinking, and is strongly associated with academic success. This result appears to be in line with recent evidence revealing that sign language interpreters are superior to the general population in abstract reasoning skills (Seal 2004). Another verbal task, Digit Span, evaluates auditory short-term working memory and concentration.…”
Section: Predictors Of Sli Proficiencysupporting
confidence: 92%
See 1 more Smart Citation
“…The verbal Similarities task measures abstract verbal reasoning and analogical thinking, and is strongly associated with academic success. This result appears to be in line with recent evidence revealing that sign language interpreters are superior to the general population in abstract reasoning skills (Seal 2004). Another verbal task, Digit Span, evaluates auditory short-term working memory and concentration.…”
Section: Predictors Of Sli Proficiencysupporting
confidence: 92%
“…♥ Aptitude mentioned for signed-language interpreters (Lara & de los Santos 2000; Frishberg 1986) a psychological profile of sign language interpreters have also shown that these professionals are cognitively superior, namely in problem solving, motor control, mental concentration, attention to detail and abstract reasoning skills (Seal 2004). No significant evidence regarding the personality of the interpreter is available so far, perhaps because there is not an "ideal" personality (Lara & de los Santos 2000: 32).…”
Section: Personality Academicmentioning
confidence: 99%
“…In a study of domain-general cognitive abilities with sign language interpreter trainees, López Gómez et al (2007) found positive correlations between interpreting skill and short-term memory, a confidence-type personality trait, and reasoning ability. However, other studies have shown that working interpreters demonstrate higher than average reasoning abilities, but that the degree of intelligence did not reliably differentiate the interpreters based on skill (Rudser & Strong 1986;Seal 2004). Similarly, examinations of working memory capacity of interpreters and interpreter students or non-interpreters have shown mixed results.…”
Section: Introductionmentioning
confidence: 92%
“…Since that time, many others have studied ASL/English interpreters to learn more about their personality. (See Bontempo, (2012); Bontempo & Napier (2014); Bontempo et al (2014); Doerfert & Wilcox (1986); Frishberg & Enders, 1974, as cited in Frishberg 1990López Gómez, Bajo Molina, & Benitez (2007); Rudser & Strong, 1986;Seal, 2004;Stauffer & Shaw, 2006). Studies show that interpreters are well-educated and bright.…”
Section: Personalitymentioning
confidence: 99%